The effect of selected massage manipulations on lactic acid elimination after anaerobic running - Taskin, M.; Budak, H.; Sanioglu, A. (International Journal of Applied Exercise Physiology, 2020)
The aim of this study was to determine whether two different massage manipulations (effleurage, friction) were applied after anaerobic running and which were more effective to the recovery level. In this study, 20 healthy football players who played in the TFF U19 elite league (mean age of 18.40±0.70 years, mean height of 1.78±0.06 m, and body weight of 70.75±966 kg) were participated in the study. Lactic acid levels were measured in 5 and 10 minutes after the anaerobic running (202.5 m) of the players. After resting for 48 hours, lactic acid levels were determined by taking blood samples from footballers before anaerobic running. The massage performed using friction technique at the removal of lactic acid after anaerobic running was more effective than massage done without massage and effleurage technique (p<0.05). In addition, friction technique was found to be more effective than effleurage technique, in massage techniques performed in fifth and tenth minutes after anaerobic running (p<0.05). As a result of this study, friction massage manipulation after anaerobic running has a more positive effect than effleurage massage manipulation, which is thought to be due to the effect of friction technique on deeper tissues.